Analysis of Drug Management Influence with the Success of Theraphy on Members of Pandangdia Community Patients with Diabetes Mellitus - Umi Athiyah; Abdul Rahem (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Drug management is essential in quality and efficacy assurance, especially to achieve therapeutic outcome of chronic diseases; such as Diabetes mellitus. This study was observational and cross-sectional. The objective of this study was to analyze the influence of drug management towards achievement of therapeutic outcome amongs patients with diabetes mellitus. Thirty-five patients (members of a community of diabetic patients in Bangkalan) were voluntarily involved in this study as respondents. A validated and reliable questionnaire was used to collect the data. The result showed that appropriate drug use and proper drug storage influenced achievement of therapeutic outcome. While, place to get medicines and infomation resource had no correlation with achievement of therapeutic outcome.